The relationship between institutional quality, industry, energy sources and environmental quality in Bangladesh: Insights from ARDL analysis - Toufique, Mohammad Mokammel Karim (Asian Journal of Empirical Research, 2024)
This study examines how institutional quality, industrial activities, energy sources, and environmental quality are connected in Bangladesh, with a particular focus on CO2 emissions from 1990 to 2015. The research aims to evaluate how these factors contribute to environmental sustainability. Using five autoregressive distributed lag (ARDL) models, the study investigates both short- and long-term connections between CO2 emissions, gross domestic product (GDP), industrial growth, and electricity generation from different sources. It also employs the Toda-Yamamoto Granger causality test to uncover the causal links between the variables. The findings reveal that higher institutional quality helps reduce CO2 emissions, while economic growth and a reliance on nonrenewable energy increase emissions. This study provides a fresh viewpoint, showing the key role of institutional quality in promoting environmental sustainability, which contrasts with some earlier research. For policymakers, the research highlights the importance of strengthening institutional frameworks, enforcing environmental regulations, and advancing the use of cleaner energy and sustainable industrial practices. These steps are essential for supporting sustainable development in Bangladesh.